Análise exploratória dos impactos de nudges fiscais nos indicadores de conformidade tributária do Programa Contribuinte Pai D'égua - Feitosa, Ricardo Cruz (2024)
This study analyzes the impact of fiscal nudges (messages of encouragement or warnings about legal consequences) on the tax compliance index of companies participating in the "Contribuinte Pai d'Égua" Program by the State Finance Department of Ceará (SEFAZ-CE). To this end, an experimental evaluation model was used, in which a representative sample of taxpayers with some fiscal irregularity was randomly assigned to three comparison groups. The first group received "positive" nudges with encouraging and friendly language. The second group received "warning" nudges, informing them about the adverse legal consequences of non-compliance. The third group (control group) did not receive any specific nudge within SEFAZ-CE's own online system. One of the distinguishing features of this research in its pilot plan was the ability to identify which taxpayers actually read the messages (in the treatment groups) or at least accessed the information system (in the control group). Using a differences-in-differences model, and further segmenting the groups by those who accessed or did not access the system, the results point to an improvement in tax compliance only for those companies that received and read warning messages. This result is consistent with findings in the literature that coercive messages have a greater effect (Antinyan and Asatryan, 2019). However, when attempting to differentiate the effect of nudges from the effect of merely accessing the system, the former lost significance.